Project manager perceptions factors influencing the delivery of successful innovation in construction projects - DIAB, MOHAMED EL SAYED (2018)
There has been an increase in the adoption of innovation in the construction industry over time. Innovation in construction is related mostly to new materials, processes, method of constructions, services, and new forms of construction organisation. Unlike in other industries, implementation of innovation is not at an organisation level but at a project level. From this point of view, there is an agreement between studies that project managers of construction projects have a significant role in innovation management at project level. In addition to that, the rate of innovation in construction is less than that of most other industries because of the nature of the industry. It is possible that less research and development might be the reason for limiting innovation growth. Therefore, this research tends to add evidence to the existing knowledge of the influence of project manager perceptions factors on delivering successful innovation at construction project level and provides important insights for further research. In this research there are 25 major items of project manager perceptions identified from the literature and categorised into four factors of project manager perceptions that most probably have an influence on innovation. This research used quantitative methodology by applying an online survey to collect data from 66 respondents that included 5 pilot samples. Ethical issues were anticipated and considered in this research. Data was collected, tested and found valid and reliable after analysis by computer software SPSS. Demographic information and the employment background of participants are relevant to this research and the respondents were considered experienced in the construction industry and familiar with project management disciplines. The main findings show that there is an influence of project manager perceptions factors on delivering successful innovation at a construction project level with evidence that his leadership, capabilities/competences, personality traits, and skills (non-engineering skills) are relatively important for the significance influence. Based on this influence, construction organisations need to adopt an innovation policy, a culture for innovation, and innovation diffusion methods which concentrate more on the characteristics of the project manager’s job and his ability to contribute or assess delivering successful innovation at project level to increase the possibilities of his influence to innovation. Also, it is recommended that construction organisations need to implement a set of selection characteristics for the position of project manager that examine his perceptions factors toward contributions in innovation. And it is recommended for the innovative client to add these characteristics to the project requirements.